2015
DOI: 10.1530/jme-15-0116
|View full text |Cite
|
Sign up to set email alerts
|

Functions of DPLIY motif and helix 8 of human melanocortin-3 receptor

Abstract: The melanocortin-3 receptor (MC3R) is a member of family A G protein-coupled receptors (GPCRs). The MC3R remains the most enigmatic of the melanocortin receptors with regard to its physiological functions, especially the role in energy homeostasis. The N/DPxxY motif and the eighth helix (helix 8) in the carboxyl terminus of GPCRs have been identified to be important for receptor expression, ligand binding, signal transduction and internalization. To gain a better understanding of the structure-function relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 84 publications
1
7
0
Order By: Relevance
“…Although these residues are remote from the binding pocket formed by residues located on the extracellular side of the MC4R [ 25 , 26 ], and likely not directly involved in receptor-ligand interaction, these mutations might induce conformational change that indirectly modulate the receptor-ligand interaction. Similar observations were made in other GPCRs as well as the MC3R and MC4R [ 20 , 27 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 84%
“…Although these residues are remote from the binding pocket formed by residues located on the extracellular side of the MC4R [ 25 , 26 ], and likely not directly involved in receptor-ligand interaction, these mutations might induce conformational change that indirectly modulate the receptor-ligand interaction. Similar observations were made in other GPCRs as well as the MC3R and MC4R [ 20 , 27 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, mutations also modify maximal responses and EC 50 values (31). The same laboratory demonstrated that a motif, DPLIY in helix 8, is important for obtaining a biased response in terms of balance between cAMP-related responses versus MAPK pathway activation (32). Mutants of the muscarinic acetylcholine M2 receptor in a model in which the cell context is nullified and the effect of the endogenous ligand is minimized, provided "evidence that downstream signaling pathways previously considered to be related to each other (i.e.…”
Section: Mechanisms Underlying Biased Receptor Functionalitymentioning
confidence: 99%
“…In structure-function studies, many artificially generated mutant MC4Rs also exhibit biased signaling in Gαs-cAMP and ERK1/2 activation [48, 49, 101]. Additionally, some naturally occurring and artificially generated mutant MC3Rs are also biased in Gαs-cAMP and ERK1/2 signaling pathways [52, 53, 102]. …”
Section: Biased Signaling At Neural Mcrsmentioning
confidence: 99%